IMPLEMENTASI ASAS NEMO PLUS YURIS SEBAGAI PERLINDUNGAN HUKUM BAGI PEMEGANG HAK ATAS TANAH (STUDI KASUS PEMBATALAN SERTIFIKAT NOMOR 2690/KEBON KELAPA) - Naomi Elvienne Yanto; Yuwono Prianto (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2018)
Since act number 5 of 1960 concerning basic regulations on agrarian principles on 24th of September 1960, it was a historic day for Indonesia. Because, that was the unification day of the land law, by revoked the land legal dualism in Indonesia for the sake to create a legal protection and also giving the legal certainty to the holders of the land rights. Likewise the act number 19 of the basic regulations on agrarian principles have instruct to held a land registration then published a land rights certificate as a proof of land ownership. It is a vigorous but not the absolute proof of land ownership, because of the impact of publication system that held in land registration in Indonesia, the land rights certificate can be canceled by a person who feels that he has rights of the land concerned. That makes the purpose of the basic agrarian principles, may not be effective due to the process of law in Indonesia concerning that basic regulations on agrarian principles concerning that it has been 58 years since the day it published.